2017
DOI: 10.1089/jop.2017.0042
|View full text |Cite
|
Sign up to set email alerts
|

Semifluorinated Alkane Eye Drops for Treatment of Dry Eye Disease Due to Meibomian Gland Disease

Abstract: Purpose: Meibomian gland disease is generally accepted as the leading cause for evaporative dry eye disease (DED). In a previous study, perfluorohexyloctane, a semifluorinated alkane, has been demonstrated to significantly increase tear film breakup time and to reduce corneal fluorescein staining in patients with evaporative DED, thereby vastly reducing dry eye-related symptoms. This study was set up to evaluate perfluorohexyloctane in a larger population of patients with Meibomian gland dysfunction.Methods: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 24 publications
5
39
0
3
Order By: Relevance
“…Those experiments show that clinical sign endpoints such as corneal fluorescein staining and TFBUT, as well as symptom endpoints (OSDI score and VAS) improved compared to baseline, indicating a good clinical efficacy of perfluorohexyloctane eye drops. 3,4 This is also reflected in the data of this trial and holds also true for the results of Schirmer I test, which increased after treatment with perfluorohexyloctane. However, although a positive treatment effect of perfluorohexyloctane eye drops was observed in the secondary endpoints, this effect failed to reach statistical significance compared to the control group.…”
Section: Influence Of Perfluorohexyloctane Eye Drops On Tftsupporting
confidence: 72%
See 1 more Smart Citation
“…Those experiments show that clinical sign endpoints such as corneal fluorescein staining and TFBUT, as well as symptom endpoints (OSDI score and VAS) improved compared to baseline, indicating a good clinical efficacy of perfluorohexyloctane eye drops. 3,4 This is also reflected in the data of this trial and holds also true for the results of Schirmer I test, which increased after treatment with perfluorohexyloctane. However, although a positive treatment effect of perfluorohexyloctane eye drops was observed in the secondary endpoints, this effect failed to reach statistical significance compared to the control group.…”
Section: Influence Of Perfluorohexyloctane Eye Drops On Tftsupporting
confidence: 72%
“…In 2 observational studies in patients with DED, treatment with perfluorohexyloctane significantly improved subjective and objective symptoms and signs of the disease. 3,4 Perfluorohexyloctane is currently also developed under the development code NOV03 under IND for the U.S. market.…”
Section: Introductionmentioning
confidence: 99%
“…F6H8 does not cause any toxic effects at the cornea and has further been shown to significantly improve clinical signs and symptoms of patients with dry eye disease. [26][27][28] Currently, the properties of SFAs as vehicles for topical drugs are under investigation. The low surface tension leads to increased spreadability across the corneal surface, which together with the longer corneal residence time compared to aqueous eye drops results in higher bioavailability of active pharmaceutical ingredients (API).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many kinds of treatments for DED have been proposed, such as Meibomian gland squeezer, polyunsaturated fatty acids, omega-3 fatty acids, perfluorohexyloctane, chitosan-N-acetylcysteine (C-NAC) and retinol palmitate [186][187][188][189][190][191]. In terms of omega fatty acids, studies demonstrated that ω-3 and ω-6 fatty acids can act directly on human Meibomian gland epithelial cells to influence the quality and quantity of intracellular lipids [192].…”
Section: Other Potential Agentsmentioning
confidence: 99%